Some aspects of goalkeepers mental conditioning in KHL hockey teams - Latipova, M.; Tukhvatullina, G.; Kamalova, E.; Agazaryan, M.; Kuznetsova, E. (BIO Web of Conferences, 2020)
A lot of things in the training of hockey players depend on their psychological state, on their psychological mood to win. Especially in extra class goalkeepers training. Responsible and highly motivated activity is always concerned about these athletes. The excitement degree for success in competitions determines the athlete`s mental state before going to the start. Even worldclass athletes cannot curb their nerves, relieve excessive nervous tension and calm down. The value of mental conditioning, complex methods on mental conditioning, risk factors in mental conditioning. Review of special educational and scientific literature, sociological survey, comparative analysis of training and competitive activities of goalkeepers in the WHL and CHL teams, mathematical processing of research data. Mental conditioning will be successful if you follow all the research materials` rules.